2011
DOI: 10.4061/2011/505239
|View full text |Cite
|
Sign up to set email alerts
|

Can Levothyroxine Be Taken as Evening Dose? Comparative Evaluation of Morning versus Evening Dose of Levothyroxine in Treatment of Hypothyroidism

Abstract: 152 drug naïve primary hypothyroid patients were divided into morning (Group 1) and evening (Group 2) dosing group and evaluated for change in biochemical profile, physical functioning and Quality of Life during the course of 12 weeks of study. At the end of 12 weeks 70 (90.90%) subjects in Group 1 and 72 (96%) in Group 2 achieved euthyroidism. On evaluation clinical symptoms and total clinical scores improved in both the groups at the end of 6 and 12 weeks. Significant improvement in thyroid profile was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 18 publications
4
47
1
2
Order By: Relevance
“…This finding favors ingestion of L-T4 during morning fast, delaying food ingestion for 30 minutes (187) (A). Conversely, recent small European and Indian studies demonstrated similar levels of thyroid hormones and no difference in clinical parameters using evening administration (188,189) (B,B), however, alimentary habits in Latin America could make these findings less applicable in our population.…”
Section: How Should Levothyroxine Be Used?contrasting
confidence: 40%
“…This finding favors ingestion of L-T4 during morning fast, delaying food ingestion for 30 minutes (187) (A). Conversely, recent small European and Indian studies demonstrated similar levels of thyroid hormones and no difference in clinical parameters using evening administration (188,189) (B,B), however, alimentary habits in Latin America could make these findings less applicable in our population.…”
Section: How Should Levothyroxine Be Used?contrasting
confidence: 40%
“…Children with GIT disorder, malabsorption syndrome or taking medication known to interfere with uptake of levothyroxine were excluded from the study. [3][4][5] Ethical clearance was obtained from the Institutional Review Board. Informed written consent was obtained from the parents of the study subjects.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 We performed this study to assess the effectiveness of bedtime levothyroxine administration as compared to morning levothyroxine administration.…”
mentioning
confidence: 99%
“…Therefore, standard recommendation is that levothyroxine should be taken an hour before breakfast on an empty stomach, to prevent interference of its uptake by food or medication (14). While taking levothyroxine in between or with food might not be best, taking it at bedtime is an-other option, as two studies have shown to have almost the same effect as when taken on an empty stomach (15,16). In contrast, a randomized crossover trail compared taking levothyroxine in the fasting state, with breakfast, or at bedtime in 65 thyroid cancer, patients with primary hypothyroidism found that fasting state and most beneficial than other times (17).…”
Section: Thyroid Hormone Replacementmentioning
confidence: 99%